Long-term patterns of relapse and survival following definitive intensity-modulated radiotherapy for non-endemic nasopharyngeal carcinoma. (February 2016) - Setton, Jeremy; Han, James; Kannarunimit, Danita; Wuu, Yen-Ruh; Rosenberg, Stephen A.; DeSelm, Carl; Wolden, Suzanne L.; Jillian Tsai, C.; McBride, Sean M.; Riaz, Nadeem; Lee, Nancy Y.
Highlights: We report long-term patterns of relapse after definitive IMRT for non-endemic NPC. 177 patients were included, including 158 who received concurrent chemotherapy. Overall, outcomes were excellent and consistent with reported short-term results. More than half of local relapses occurred after 2 years. Our results highlight critical importance of long-term multidisciplinary follow-up. Summary: Background: We report treatment outcomes for a large non-endemic cohort of patients with nasopharyngeal carcinoma treated with intensity-modulated radiotherapy (IMRT) and chemotherapy. Methods: We identified 177 consecutive patients with newly diagnosed, non-metastatic nasopharyngeal cancer treated with definitive IMRT between 1998 and 2011. Endpoints included local, regional, distant control, and overall survival. Results: Median follow-up was 52 months. The 3-/5-year actuarial rates of local control, regional control, distant control, and overall survival were 92%/83%, 93%/91%, 86%/83%, and 87%/74%, respectively. The median time to local recurrence was 30 months; the annual hazard of local recurrence did not diminish until the 6th year of follow-up. Conclusions: Overall, we observed excellent rates of disease control and survival consistent with initially reported results from our institution. Attaining locoregional control in patients with extensive primary tumors remains a significant clinical challenge. With mature follow-up we observed that more than half of observed local relapses occurred after 2 years, a pattern distinct from that of carcinomas arising from other head and neck sites. These findings raise the possibility that patients with NPC may benefit from close follow-up during post-treatment years 3–5.